Exploring Bidirectional Causality between Obstructive Sleep Apnea and Chronic Kidney Disease via Mendelian Randomization - Liu X; Liu M; Zhong B; He X; Xu Y; Zhou Z; Qin P (Nature and Science of Sleep)
Xiaoning Liu,1 Mengna Liu,2 Bijuan Zhong,3 Xinxin He,2 Yalai Xu,1 Zheng Zhou,1 Pei Qin4 1Department of Respiratory and Critical Care Medicine, The Second Affiliated Hospital of Zhengzhou University, Zhengzhou, Henan, 450014, People’s Republic of China; 2School of Public Health, Zhengzhou University, Zhengzhou, Henan, 450001, People’s Republic of China; 3School of Public Health, Shantou University, Shantou, Guangdong, 515063, People’s Republic of China; 4Center for Clinical Epidemiology and Evidence-Based Medicine, Shenzhen Qianhai Shekou Free Trade Zone Hospital, Shenzhen, Guangdong, 518001, People’s Republic of ChinaCorrespondence: Zheng Zhou, Department of Respiratory and Critical Care Medicine, The Second Affiliated Hospital of Zhengzhou University, Zhengzhou, Henan, 450000, People’s Republic of China, Email zhouzheng3316@zzu.edu.cn Pei Qin, Center for Clinical Epidemiology and Evidence-Based Medicine, Shenzhen Qianhai Shekou Free Trade Zone Hospital, Shenzhen, Guangdong, 518001, People’s Republic of China, Email qinpei225@163.comPurpose: It remains unclear about the causal association between obstructive sleep apnea (OSA) and chronic kidney disease (CKD) and renal function. This study aimed to explore the bidirectional causal relationship between OSA and CKD and renal function.Methods: We used a 2-sample bidirectional Mendelian randomization (MR) method to evaluate the causal relationship between OSA and estimated glomerular filtration rate from creatinine (eGFRcrea), eGFR from cystatin C (eGFRcys), urine albumin to creatinine ratio (UACR), blood urea nitrogen (BUN), and chronic kidney disease (CKD). Inverse variance weighted (IVW), MR-Egger, weighted median, MR-Egger, and pleiotropy residual sum and outlier test (MR-PRESSO) were used to calculate the β or odds ratio [OR] and their 95% CIs.Results: Genetically predicted OSA was found to be associated with BUN (β=0.040, 95% CI: 0.013– 0.067, p = 0.003), but not associated with CKD (OR = 1.075, 95% CI: 0.916– 1.263, p = 0.375), eGFRcrea (β=0.007, 95% CI: − 0.004– 0.017, p = 0.203), eGFRcys (β=− 0.012, 95% CI: − 0.026– 0.002, p = 0.102), or UACR (β=− 0.025, 95% CI: − 0.058– 0.007, p = 0.122). In the reverse analysis, genetically predicted eGFRcys (OR, 0.687; 95% CI, 0.497– 0.950, p = 0.023) and BUN (OR, 1.686; 95% CI, 1.299– 2.073, p = 0.008) was associated with an increased risk of OSA. The Cochrane’s Q test reveals significant heterogeneity between various single nucleotide polymorphisms. MR-Egger indicated no evidence of genetic pleiotropy. Results were robust using other MR methods in sensitivity analyses.Conclusion: Through the two-sample MR analysis, we identified kidney function may have a causal relationship with OSA, but a causal relationship between OSA and CKD and kidney function remains uncertain. More studies are required to better understand the relationship between OSA and CKD and kidney function.Keywords: obstructive sleep apnea, chronic kidney disease, renal function, bidirectional, Mendelian randomization